Position of the Tax Court Under the State Administrative Court - Anggraeni, RR Dewi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2023)
The Tax Court in Indonesia is within the State Administrative Court (PTUN), facing the complexity of tax disputes that require careful and accurate handling. This research explores the position of the Tax Court within the PTUN framework, highlighting the challenges and opportunities faced in dealing with changes in tax laws and regulations. This study seeks to analyze the impact of changes in statutory regulations on the Tax Court and identify strategies to enhance the effectiveness and quality of Tax Court decisions in addressing tax dynamics. This study employs qualitative methods and a legal and scholarly approach. The relevant literature and pertinent laws and regulations are analyzed to understand the issues discussed thoroughly. The research findings indicate that the Tax Court, as an integral part of the PTUN, confronts complex challenges stemming from alterations to tax laws. This study identifies opportunities for enhancing judge training, employing information technology, and collaborating closely with tax agencies. In addressing these obstacles, the Tax Court can ensure equitable, accurate, and consistent decisions, preserve the integrity of the tax justice system, and cultivate public confidence.